NeuroAI winning the minds of consumers with neuroscience powered GenAI - Pradeep, A. K. 1963-; Chakravarty, Rajat; Acharya, Anirudh; Dev, Ratnakar (Ascent Audio, 2024)
Neuroscience-powered GenAI enables massive impact on everything from medicine to marketing, entertainment to education, flavors to fragrances, and much more. Simply by blending cutting edge neuroscience with bleeding edge GenAI. Put humanity back at the center of GenAI. NeuroAI is the master guide for everyone seeking to understand this breakthrough technology; what it is, how it works, and most especially how to put it to work for competitive advantage in the marketplace. For business leaders and all who seek expert insight and practical guidance on how to harness this astounding technology with maximum effect for business and personal success, NeuroAI serves as an inspiring and accessible resource for successful marketing in the Age of the Machine.
Online resource; title from title details screen (O'Reilly, viewed October 29, 2024)
Keywords: Artificial intelligence -- Marketing applications; Consumers -- Psychology; Intelligence artificielle; Applications en marketing; Consommateurs; Psychologie; Audiobooks; Livres audio